Extension and Sustainable Development in Globalization Conditions - Kudinova, Iryna (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2017)
The theoretical aspects of sustainable development are considered in the article. Its essence and features are exposed in the agrarian sector of economics. It is well-proven that sustainable development of territory depends on sustainability of economic, social and ecological factors and sent to satisfaction of necessities present and future generations. The Extension service (informatively-consultative) of sustainable development of agriculture is reasonabled. The primary objective of sustainable development of territory is providing of accumulation of resource possibilities for realization of the extended recreation and increase of level of welfare of population without harm to the environment. Creation of research and information centers and scientifically-educational establishments is offered on questions sustainable development and centers of the best practices of sustainable development.